Description of Goffacarus n. gen., to Reallocate the Species Euschoengastia latchmani Brennan and Yunker and Euschoengastia obscura Wrenn and Loomis (Trombidiformes: Trombiculidae) - Bassini-Silva, Ricardo (2021)
Purpose: Euschoengastia Ewing is a chigger genus in need of revision as it historically has combined species solely on the presence of expanded prodorsal trichobothria. The objective of the present study is to describe a new genus to reallocate two North American Euschoengastia species, to start an organization into this genus. Methods : In this study, we provide drawings, measurements and microscopy images on a Microscope Zeiss for the two redescribed species. Results: After examining the types of the species Euschoengastia latchmani Brennan and Yunker and Euschoengastia obscura Wrenn and Loomis, we realized that it was necessary to create the new genus to relocate these two species, mainly based on the following characters: (1) the number of prongs on the odontus; and (2) ornamentation of the prodorsal sclerite. Conclusion: Goffacarus latchmanin. comb. and Goffacarus obscuran. comb. are redescribed here and to reallocate these two species the genus, Goffacarusn. gen. is proposed.